Integrating the STEAM Approach in Early Childhood Education to Develop Critical and Creative Thinking Skills - Nurtina Irsad Rusdiani (Journal of Gemilang, 2026)
The development of critical and creative thinking skills has become an important priority in early childhood education as part of preparing children to face the challenges of the twenty-first century. Early childhood learning environments should therefore encourage exploration, problem-solving, and creativity through meaningful and interactive activities. One innovative approach that supports these objectives is the STEAM approach, which integrates Science, Technology, Engineering, Arts, and Mathematics into interdisciplinary learning experiences. This study aims to analyze how the integration of the STEAM approach in early childhood education contributes to the development of children’s critical and creative thinking skills. This research employs a mixed-method approach involving qualitative and quantitative analysis. Data were collected through classroom observations, teacher interviews, and documentation of STEAM-based learning activities conducted with children aged 4–6 years in early childhood education settings. The collected data were analyzed using thematic analysis for qualitative findings and descriptive statistics to examine improvements in children’s thinking skill indicators. The findings indicate that STEAM-based learning significantly improves children’s ability to observe, ask questions, experiment, generate original ideas, and collaborate in problem-solving activities. These learning experiences also enhance children’s engagement, creativity, and early scientific literacy through hands-on exploration and interdisciplinary activities. In conclusion, the integration of the STEAM approach in early childhood education effectively supports the development of critical and creative thinking skills while creating meaningful and engaging learning environments for young learners